Methylene Blue Has Strong Extracellular Virucidal Activity Against a SARS-CoV-2-Related Pangolin Coronavirus with No Intracellular or In Vivo Efficacy - Lai Wei; Yuezhen Ma; Yuhao Ren; Shanshan Lu; Xiumei Xiao; Shengdong Luo; Xiaoping An; Erguang Li; Huahao Fan; Lihua Song (Pathogens)
Studies have demonstrated that methylene blue exhibits significant antiviral activity against SARS-CoV-2 or related coronaviruses at the cellular level, suggesting its potential as an anti-SARS-CoV-2 drug. Herein, we report that methylene blue does not exhibit noticeable antiviral activity in a lethal model involving SARS-CoV-2-related pangolin coronavirus GX_P2V (short_3UTR) infection in CAG-hACE2 transgenic mice. We employed plaque reduction assays and cell infection experiments to compare the extracellular virucidal activity of the compound and its ability to inhibit viral replication in cells to those of nirmatrelvir. Methylene blue demonstrated strong virucidal activity but did not inhibit viral replication in cells. The control compound nirmatrelvir lacked virucidal activity but exhibited strong abilities to inhibit viral replication. The virucidal activity of methylene blue was further tested in mouse plasma. Incubation in mouse plasma increased the virucidal EC50 value of methylene blue, indicating that mouse plasma can affect the stability of the compound, although mouse plasma has some extent of natural virucidal activity. These findings elucidate why methylene blue lacks antiviral efficacy in vivo and provide insights for the development of antiviral drugs.